Distinct immune evasion in APOBEC‐enriched, HPV‐negative HNSCC. Issue 8 (18th June 2020) - Messerschmidt, Clemens; Obermayer, Benedikt; Klinghammer, Konrad; Ochsenreither, Sebastian; Treue, Denise; Stenzinger, Albrecht; Glimm, Hanno; Fröhling, Stefan; Kindler, Thomas; Brandts, Christian H.; Schulze‐Osthoff, Klaus; Weichert, Wilko; et al.
Abstract: Immune checkpoint inhibition leads to response in some patients with head and neck squamous cell carcinoma (HNSCC). Robust biomarkers are lacking to date. We analyzed viral status, gene expression signatures, mutational load and mutational signatures in whole exome and RNA‐sequencing data of the HNSCC TCGA dataset (n = 496) and a validation set (DKTK MASTER cohort, n = 10). Public single‐cell gene expression data from 17 HPV‐negative HNSCC were separately reanalyzed. APOBEC3‐associated TCW motif mutations but not total single nucleotide variant burden were significantly associated with inflammation. This association was restricted to HPV‐negative HNSCC samples. An APOBEC‐enriched, HPV‐negative subgroup was identified, that showed higher T‐cell inflammation and immune checkpoint expression, as well as expression of APOBEC3 genes. Mutations in immune‐evasion pathways were also enriched in these tumors. Analysis of single‐cell sequencing data identified expression of APOBEC3B and 3C genes in malignant cells. We identified an APOBEC‐enriched subgroup of HPV‐negative HNSCC with a distinct immunogenic phenotype, potentially mediating response to immunotherapy. Abstract : What's new? Head and neck squamous cell carcinoma (HNSCC) is sometimes susceptible to immune checkpoint inhibitors, and biomarkers are needed to help identify which tumors are most likely to respond. Using the Cancer Genome Atlas, these authors evaluated 496 HSNCCs by HPV status, gene expression signatures, mutational load, and mutational signatures. They found that increased inflammation was associated with APOBEC3‐induced mutations in HPV‐negative cancers. This newly identified APOBEC‐enriched, HPV‐negative subgroup showed higher immune checkpoint expression, and also more mutations in immune‐evasion pathways, suggesting this may be a way to identify candidates for immune checkpoint inhibitor therapy.